A novel hybrid multi-criteria decision-making model to assess a stairs shape for dwelling houses. Issue 8 (16th November 2016) - Turskis, Zenonas; Juodagalvienė, Birutė
Abstract: The paper presents a novel approach to solve problem of stairs shape assessment for two-story individual dwelling houses. Selection among available shapes and construction of stairs is a multi-criteria decision-making problem in nature. It depends on a set of different conflicting criteria, that have different optimisation direction, different measurement units. There is determined the set of the main criteria to assess the alternatives is as follows: Stairwell Area, The Total Area of Climbing, "Climbing Lane" Area, The Cost of Stairs, and Ergonomics. A novel original hybrid MCDM (multi-criteria decision-making) model, which based on ten different multi-criteria decision-making methods: Game Theory, AHP, and SAW, Multiplicative Exponential Weighting, TOPSIS, and EDAS, ARAS, Full Multiplicative form, Laplace Rule, and Bayes Rule, is presented.